Writing between the lines : portraits of Canadian anglophone translators - Whitfield, Agnès, 1951- (Wilfrid Laurier University Press, 2006)
The essays in Writing between the Lines explore the lives of twelve of Canada's most eminent anglophone literary translators, and delve into how these individuals have contributed to the valuable process of literary exchange between francophone and anglophone literatures in Canada. Through individual portraits, this book traces the events and life experiences that have led W.H. Blake, John Glassco, Philip Stratford, Joyce Marshall, Patricia Claxton, Doug Jones, Sheila Fischman, Ray Ellenwood, Barbara Godard, Susanne de Lotbinire-Harwood, John Van Burek, and Linda Gaboriau into the complex w.